Microtremor analysis to identify fissure vulnerable zones in Demak, Central Java, Indonesia - Leonita, Rahmadany; Sismanto,; Marjiyono, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Demak Regency, located in Central Java, Indonesia stands out among the regencies for its rapid development and regional growth, leading to a significant reliance on groundwater. This is thought to be caused by low precipitation and the geological characteristics of Demak Regency, which is mostly located on alluvial plains. To address these concerns, this study aimed to pinpoint regions vulnerable to ground fractures resulting from excessive groundwater extraction compounded by seismic activity. The research encompassed 191 locations, including 177 single station microtremor measurement points and 14 array microtremor measurement points. Single station microtremor measurements utilized the Horizontal to Vertical Spectral Ratio (HVSR) method, while array measurements employed the Spatial Autocorrelation (SPAC) method. Ground shear strain values spanning from 32.12 × 10-6 - 96.39 × 10-6. Notably, areas exhibiting heightened values are concentrated in Wonosalam Subdistrict and the Southwest of Karangtengah Subdistrict. The morphology of the bedrock within the study area tends to mirror the sedimentary layer’s thickness, reflecting relatively minimal surface height discrepancies at the measurement points. Vulnerability to fissures resulting from excessive groundwater extraction and seismic activity is concentrated on the north side of Wonosalam District, the eastern sector of Demak District, and a small section of Mijen District.